Síndrome de Down: caminhos da vida - Casarin, Sonia (2007)
This study discusses the relational universe of the person with Down syndrome, checking on the relation between developmental needs and the interactional context, and tries to understand the mutual influences between the person and these contexts. Down syndrome leads to major developmental changes and its effects can be reduced by the stimulation of the various aspects of development. The joint stimulation, done by the union of all the people and contexts involved, can lead to much more benefits for the person who has the syndrome. For the Bioecological Model of Human Development, the development is the result of the joint function of person, process, context and time. This integrated approach to the human development has been adequate to study the relation of the development needs and interactional contexts within the Down syndrome. The study was made with four participants that have the Down syndrome, all in different life cycle phases, that is, childhood, adolescence, adulthood and oldness. Besides the people with the syndrome, the study involved other aspects of their lives, as families, schools, jobs and sport activities. The research was made trough case studies and interview was used to collect the data. The collected data was analyzed through the Bioecological Model and the results showed that during all life cycle phases the family is the main stimulus of human development, specially for people with Down syndrome. The main society characteristics influences the way in which the family will use its resources. When the general context conditions are adverse, the family resources are found within the family social network. When the social conditions are favourable to, the family will choose between the multiple services offered by the community, considering what she believes it s more satisfactory for their children. The conditions offered by the society do not guarantee the path the family group will attend, for many options are made by personal and family characteristics. In this matter, besides the social opportunities, the family can live ambiguities and contradictions that will influence the person who has the Down syndrome